Efficient Propagation of Equine Viruses in a Newly Established Equine Cell Line, FHK-Tcl3.1 Cells - OGUMA, Keisuke; ISHIDA, Maiko; MAEDA, Ken; SENTSUI, Hiroshi (Journal of Veterinary Medical Science, 2013)
Equine cells are required for isolation of viruses that infect the horse. However, only a few equine cell lines and cell cultures are available so far. Fetal horse kidney (FHK)-Tcl3.1 cell is a novel cell line established by introducing simian virus 40 (SV40) large T antigen. In the present study, the ability to propagate equine viruses was compared between FHK-Tcl3.1 cells and other equine cells. FHK-Tcl3.1 cells efficiently increased many viruses derived from or having pathogenicity to horses and produced high infective titers in culture fluids. These results indicate that FHK-Tcl3.1 cells would be useful for propagation and serological tests of viruses that affect Equidae.